2021
DOI: 10.3354/meps13654
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic shifts in home range size of a top predatory reef-associated fish (Caranx ignobilis): implications for conservation

Abstract: De ning the home range of vulnerable species is critical for designing effective spatial management strategies. However, animal home ranges often change with ontogeny and quantifying the associated temporal and spatial changes is particularly challenging for mobile marine species. Here, we investigate how the space use of a top predatory reef-associated sh (Caranx ignobilis) scales with body size. We tagged 17 individuals, representing a wide range of sizes (40.5-120 cm fork length (FL)), with acoustic transmi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The probability of occurrence of large fishes, however, displayed a weaker response to the effect of NTMR protection, a result that can be partly explained by the generally low number of individuals observed in the samples, as well as their potential larger home range size and mobility (Daly et al. 2021 ), which may not be captured adequately by small reserves (Claudet et al. 2010 ; Edgar et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The probability of occurrence of large fishes, however, displayed a weaker response to the effect of NTMR protection, a result that can be partly explained by the generally low number of individuals observed in the samples, as well as their potential larger home range size and mobility (Daly et al. 2021 ), which may not be captured adequately by small reserves (Claudet et al. 2010 ; Edgar et al.…”
Section: Discussionmentioning
confidence: 99%
“…Our assemblage-level model demonstrated that the network of NTMRs around Australia can enhance ecological benefits by boosting the relative abundance of individuals above the MLS across a broad array of species and ecosystem configurations. The probability of occurrence of large fishes, however, displayed a weaker response to the effect of NTMR protection, a result that can be partly explained by the generally low number of individuals observed in the samples, as well as their potential larger home range size and mobility (Daly et al 2021), which may not be captured adequately by small reserves (Claudet et al 2010;Edgar et al 2014). For instance, NTMRs had a strong effect on the probability of occurrence of large-bodied individuals of coral trout (Plectropomus spp.…”
Section: Figurementioning
confidence: 95%
“…Designing effective methods to observe fish movement is not a trivial task; the underwater world differs immensely from the terrestrial realm, and methods of visual surveillance, identification and tracking come with complex challenges for the fish biologist. Nonetheless, a proper understanding of spatial requirements of fish remains at the forefront of designing, implementing and evaluating effective conservation management strategies (Daly et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Differences between these metrics, and those often described in batchmarking studies, are important; unable to monitor individual fish, batch-marking metrics are often derived from movement distances rather than the area over which a fish ranges. Individual tracking offers many benefits over traditional batch-marking designs; individual fish can be monitored, facilitating attribution of behaviours and spatial patterns to individual characteristics such as fish size, sex or previous locations (Pillans et al 2017;Daly et al 2021). As technology advances and transmitters become smaller and cheaper, more studies are able to implement this design rather than traditional batch-marking approaches .…”
Section: Introductionmentioning
confidence: 99%